2018
DOI: 10.1080/02648725.2018.1471566
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNAs: regulation, function and cancer

Abstract: Long noncoding RNAs (lncRNAs) are non-protein-coding RNA transcripts that exert a key role in many cellular processes and have potential toward addressing disease etiology. Here, we review existing noncoding RNA classes and then describe a variety of mechanisms and functions by which lncRNAs regulate gene expression such as chromatin remodeling, genomic imprinting, gene transcription and post-transcriptional processing. We also examine several lncRNAs that contribute significantly to pathogenesis, oncogenesis,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 184 publications
0
82
0
1
Order By: Relevance
“…Mounting evidence has demonstrated that epigenetic regulation of lncRNAs plays important roles in human cancer progression, and may hold the key to developing novel molecular target for cancer treatment. [10][11][12] In the present study, we presented new data, showing lncRNA NORAD is upregulated in human EOC and inhibiting NORAD could yield tumor-suppressing functions in EOC cells through endogenously competition against hsa-miR-155-5p.…”
Section: Discussionmentioning
confidence: 70%
“…Mounting evidence has demonstrated that epigenetic regulation of lncRNAs plays important roles in human cancer progression, and may hold the key to developing novel molecular target for cancer treatment. [10][11][12] In the present study, we presented new data, showing lncRNA NORAD is upregulated in human EOC and inhibiting NORAD could yield tumor-suppressing functions in EOC cells through endogenously competition against hsa-miR-155-5p.…”
Section: Discussionmentioning
confidence: 70%
“…On the other hand, miRNA, a class of short noncoding RNAs, have been shown to regulate translation of mRNAs by capturing them for degradation by RNA‐induced silencing complex or by sequestering them into GW/P‐bodies, stress granules, or other structures for later translation. Competing endogenous RNA, also known as ceRNAs (Rafiee et al, ), could bind to miRNAs and reduce its availability for binding to its target mRNA. In our study, we showed that lncRNA MALAT1 could sponge miR‐558, reducing its binding availability to ULK1 mRNA, in turn upregulating the expression levels of ULK1 mRNA.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, miRNA, a class of short noncoding RNAs, have been shown to regulate translation of mRNAs by capturing them for degradation by RNA-induced silencing complex or by sequestering them into GW/P-bodies, stress granules, or other structures for later translation. Competing endogenous RNA, also known as ceRNAs (Rafiee et al, 2018), could bind to miRNAs and F I G U R E 6 The effects of lncRNA MALAT1 on cardiomyocytes injuries in vivo. (a) WT-and MALAT1-knockout (MALAT1 −/− ) mice were treated with PBS or ISO as described in Section 2, and after they were killed, the expression levels of MALAT1 and miR-558 in myocardial tissues were determined by qRT-PCR.…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNA field is in its infancy yet from what we do know we find that lncRNAs play critical roles in a wide variety of biological processes and diseases from cell differentiation, tissue organ development, flowering in plants, to cancer metastasis to name just a few [26][27][28][29][30]. We believe that lncRNAs play regulatory roles in many biological processes and diseases.…”
Section: The Biological Questionmentioning
confidence: 99%